Scientific recreations to favor the learning of the periodic table in high school students with incomplete schooling - Castro Valdiviezo, Havdih; Batista Zaldívar, Mario Adelfo (Eclética Química, 2023)
Didactic games for science teaching contribute to student learning and break with traditional teaching models. The objective of this study was to implement a didactic guide with scientific recreations to favor the learning of the periodic table in students with incomplete schooling in the 2022–2023 school year. For this purpose, an experimental, field and explanatory research was used. A population study was carried out with 60 students of the first year of high school of the “Velasco Ibarra” Fiscal Educational Unit. The main theoretical and empirical methods were used, as well as descriptive and inferential statistics for data processing, analysis and interpretation. A didactic guide with scientific recreations was elaborated to favor the learning of the periodic table in students with unfinished schooling, which was applied to the students of the “Velasco Ibarra” Fiscal Educational Unit, in the 2022–2023 school year. It was corroborated that the didactic guide with scientific recreations applied significantly improved the students’ learning of the periodic table.